Analysis of Wild Type LbCpf1 Protein, and PAM Recognition Variants, in a Cellular Context - Shin, Ujin; Brondani, Vincent (Frontiers in Genetics, 2021)
Nucleases used in genome engineering induce hydrolysis of DNA phosphate backbone in a sequence-specific manner. So far CRISPR-Cas, the RNA-guided nucleases, is the most advanced genome engineering system. The CRISPR nucleases allows recognition of a particular genomic sequence with two distinct molecular interactions: first, by direct interaction between the nuclease and the protospacer-adjacent motif, wherein discrete amino acids interact with DNA base pairs; and second, by hybridization of the guide RNA with the target DNA sequence. Here we report the application of the single strand annealing cellular assay to analyze and quantify nuclease activity of wild type and mutant CRISPR-Cpf1. Using this heterologous marker system based on GFP activity, we observed a comparable PAM recognition selectivity with the NGS analysis. The heterologous marker system has revealed that LbCpf1 is a more specific nuclease than AsCpf1 in a cellular context. We controlled the in vitro activity of the Cpf1 nuclease complexes expressed in mammalian cells and demonstrated that they are responsible of the DNA cleavage at the target site. In addition, we generated and tested LbCpf1 variants with several combinations of mutations at the PAM-recognition positions G532, K538 and Y542. Finally, we showed that the results of the in vitro DNA cleavage assay with the wild type and mutants LbCpf1 corroborate with the selection of 6TG resistant cells associated to the genomic disruption of hprt gene.